A Method to Compare the Activities of Semiconductor Photocatalysts in Liquid−Solid Systems. Issue 11 (17th August 2018) - Megatif, Lena; Dillert, Ralf; Bahnemann, Detlef W.
Abstract: A method to determine the activity of semiconducting photocatalysts in liquid–solid systems is suggested employing a black body photoreactor. The reaction rates, defined as the converted amount of the probe molecule per unit time (d n /d t ), in the presence of nine different photocatalysts, were found to be constant and not affected by the initial concentration of the probe compound dichloroacetic acid ( c 0 ), the mass concentration of the photocatalyst ( γ ), and the suspension volume (when c 0 and γ are larger than 5 mM and 1 g L −1, respectively). The method presented here thus seems to be generally applicable to obtain experimental data allowing the comparison of the photocatalytic activities of different semiconductors. Abstract : Compare and contrast : A comparative assessment of semiconductor photocatalysts for application in aqueous suspensions was performed employing a black body photoreactor. It was found that reaction rates were not affected by the concentration of the probe compound, the mass concentration of the photocatalyst, or the suspension volume.